Use of aerosol therapy in pulmonary diseases - Grabicki, Marcin; Batura-Gabryel, Halina (Przewodnik Lekarza/Guide for GPs, 2008)
The use of inhaled aerosol medications for the treatment of pulmonary diseases, which has become well established in the last fifty years, has advantages over oral and parenteral routes of delivery. Aerosol therapy allows selective and effective treatment of the lungs directly by achieving high drug concentration in the airway while reducing systemic adverse effects by minimizing systemic drug levels. Nowadays there are several groups of medications which can be successfully used in aerosol delivery devices. The new technical solutions in production of inhalation devices have resulted in increased drug deposition in the lungs and in better effectiveness of respiratory tract disease management.